Musculoskeletal disorders, stress, and life quality in professors of Servicio Nacional de Aprendizaje (2022)
ABSTRACT: Objective. This research aimed to stablish the relationship between musculoskeletal disorders, stress, and quality of life of professors at a Servicio Nacional de Aprendizaje campus. Materials and methods. The study was quantitative, non-experimental, descriptive. The sample was constituted by 55 professors, selected by a simple random sample. The instruments used were the Nordic Musculoskeletal Questionnaire, the stress questionnaire of Colombia´s Ministry of Health and Social Protection, and the Quality of Life Test, WhoQol Bref - Spanish version, authorized by the Word Health Organization. The data analysis was in SPSS-23, based on descriptive statistics (median and interquartile range) and correlative statistics (r Pearson and Rho Spearman), considering the normal distribution, which is calculated according to the Kolmogorov-Smirnov test. Results. Positive relationship and a statistically significant association were found between musculoskeletal disorders and stress symptoms and general stress (p<0,5 and p<0,01). Negative correlation and statistical association were also found between musculoskeletal disorders and most domains of quality of life, as well as similar results when stress was related to quality of life (p <0.5 and p <0.01).Conclusion. It was found that the greater the presence of musculoskeletal disorders and stress, the lower the quality of life in the teachers participating in the study.